2018
DOI: 10.1159/000481087
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Women with Breast Cancer Get Diagnosed and Treated Late in Sub-Saharan Africa Perspectives from Women and Patients in Bamako, Mali

Abstract: Background: Breast cancer, the most common cancer among women worldwide, has a high mortality rate in low-income countries. In sub-Saharan Africa, most breast cancer patients are diagnosed with advanced disease. Some studies have quantified the time delay to diagnosis in sub-Saharan Africa, but very few have used qualitative methods to understand barriers leading to delay. This study analyses barriers throughout a breast cancer patient's pathway from symptom recognition to treatment in Mali. Method: Three focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 28 publications
2
50
1
1
Order By: Relevance
“…Some reasons for late presentation in SSA include low breast cancer awareness, difficult access to healthcare (both physical and economic), fear, distrust of conventional medicine and belief in alternative sources of healing . Additionally, pathways within the healthcare system often hinder early diagnosis . Unfavorable tumor biology such as triple‐negative disease or the luminal‐B‐like phenotype may also be associated with late stage presentation, as these tumors generally grow faster leading to late stage at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reasons for late presentation in SSA include low breast cancer awareness, difficult access to healthcare (both physical and economic), fear, distrust of conventional medicine and belief in alternative sources of healing . Additionally, pathways within the healthcare system often hinder early diagnosis . Unfavorable tumor biology such as triple‐negative disease or the luminal‐B‐like phenotype may also be associated with late stage presentation, as these tumors generally grow faster leading to late stage at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…23,30 Additionally, pathways within the healthcare system often hinder early diagnosis. 31,32 Unfavorable tumor biology such as triplenegative disease or the luminal-B-like phenotype may also be associated with late stage presentation, 33 as these tumors generally grow faster leading to late stage at diagnosis. Furthermore, the possibility of underestimation of Stage IV disease due to the paucity of facilities for accurate staging needs to be considered in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is low awareness about cancers and limited access to treatment modalities including surgery and radiotherapy in Uganda and most sub Saharan African countries . Previous bad experiences with and mistrust in health facilities potentially make the catchment communities delay help‐seeking . Other factors that may make people not seek care in health facilities are fears related to a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Previous bad experiences with and mistrust in health facilities potentially make the catchment communities delay help-seeking. 11,12 Other factors that may make people not seek care in health facilities are fears related to a cancer diagnosis. A systematic review of 102 studies from 26 countries showed that people fear a cancer diagnosis because cancer is considered a vicious, unpredictable enemy that attacks unannounced, and often leads to death of the victims.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in SSA including SA have explored pathways to breast and cervical cancer diagnosis including late presentation among women attending health care facilities who have been diagnosed with breast or cervical cancer [15,16,19,20]. To our knowledge no published studies have explored women's appraisal, interpretation and help-seeking behaviour for possible symptoms of breast and cervical cancer within a community setting with women currently or recently experiencing symptoms.…”
Section: Introductionmentioning
confidence: 99%